2002
DOI: 10.1034/j.1600-0528.2002.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Reported bruxism and stress experience

Abstract: The aim of the study was to analyze whether perceived bruxism was associated with stress experience, age, gender, work role, and occupational health care use among a nonpatient multiprofessional population. Altogether, 1784 (age 30-55 years) employees of the Finnish Broadcasting Company were mailed a self-administered questionnaire covering demographics, perceived bruxism, total stress experience and the use of health care services provided by the company. The response rate was 75% (n = 1339, 51% men) and mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
77
2
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 16 publications
12
77
2
7
Order By: Relevance
“…Finally, stress has been considered an important initiating, predisposing and perpetuating factor of bruxism [16]. A study on 1784 employees in various work positions showed that the experience of severe stress was significantly associated with the frequency of bruxing events [16]. Electromyographic studies showed a pronounced increase of masseter activity following stressful stimuli such as noise exposure in bruxism patients suggesting an increased responsiveness to stressors [17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, stress has been considered an important initiating, predisposing and perpetuating factor of bruxism [16]. A study on 1784 employees in various work positions showed that the experience of severe stress was significantly associated with the frequency of bruxing events [16]. Electromyographic studies showed a pronounced increase of masseter activity following stressful stimuli such as noise exposure in bruxism patients suggesting an increased responsiveness to stressors [17].…”
Section: Discussionmentioning
confidence: 98%
“…These stimuli might enhance catecholamine synthesis [14] and thus increase sympathetic tone. Finally, stress has been considered an important initiating, predisposing and perpetuating factor of bruxism [16]. A study on 1784 employees in various work positions showed that the experience of severe stress was significantly associated with the frequency of bruxing events [16].…”
Section: Discussionmentioning
confidence: 99%
“…We agree with Bracha et al that many authors consider sympathetic activation a precursor of bruxism. We quoted several of these articles in our manuscript [1,2,4,5]. However, we also suggested that the increased sympathetic activity might be the effect of tooth grinding and secondary to bruxism related chronic orofacial pain and tension headache.…”
mentioning
confidence: 80%
“…Although most authors agree that sympathetic activity is increased in bruxism patients [2,5,6], there might be some discrepancy whether increased sympathetic activity is cause [1,2,4,5] or result of tooth grinding.…”
mentioning
confidence: 87%
“…In Selbstberichtsmaßen konnte ein Zusammenhang gefunden werden: Bruxierer berichten über ein größeres Stresserleben [z.B. Hicks und Conti, 1991;Ahlberg et al, 2002]. Auch konnte ein Zusammenhang zwischen erhöhten Stresshormonen und nächtlicher bruxistischer Aktivität gefunden werden [Clark et al, 1980].…”
Section: Stress Als äTiologischer Faktorunclassified